PERANAN HUKUM DALAM PERCEPATAN PEMBANGUNAN EKONOMI - Adiputra, Rizky; Surwita, Tata; Nuraeni, Ummi; Yogaswara, Yanuardi; Rokhmat, Farid; Ruslina, Elli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The concept of economic law is a legal arrangement in the field of economics and not law in the sense of economic determination that arises in economic activities (economics). These two things almost mean the same when we first hear the term economic law. The law of economic development is motivated by the rapid growth and development of economic activities in almost all parts of the world. So that the question arises how economic law functions in legal development in Indonesia and the role of law in today's national development. The research method used is normative juridical which views the law as what is contained in laws and regulations or rules that set acceptable standards of human behavior. This research method focuses on the analysis of existing legal norms (Amiruddin & Asikin, 2021). The research approach used is the statute approach. The results of the study show that economic law is part of the legal system in Indonesia and plays a very big role in regulating economic activities in Indonesia as something very fundamental, so we can easily find various laws and regulations in Indonesia. It is clear that it is not only the economic field that must be dealt with conceptually, systemic and professionally. Referring to matters of national economic development that rely on technological advances and communication in the era of the Industrial Revolution 4.0 in the legal field, especially in the preparation and design of a law or regulation, predictions or forecasts can be made using systems owned by technology and communication.Keywords: Law, Economy, Development